Addressing Hypertension and Diabetes through Community-Engaged Systems (ANDES) in Puno, Peru: rationale and study protocol for a hybrid type 2 effectiveness and implementation randomized controlled trial - Lindsay J. Underhill; Kendra N. Williams; Lucy Cordova-Ascona; Karina Campos; Lisa de las Fuentes; Mark D. Huffman; Joel Gittelsohn; Kenneth B. Schechtman; Zoila Vela-Clavo; Carla Tarazona-Meza; Laura K. Beres; Parker K. Acevedo; et al. (Trials)
Abstract Background Hypertension is the most common cardiovascular disease in Peru despite the availability of cost-effective, evidence-based treatment. Here we describe the rationale and study design for a hybrid type 2 randomized controlled trial to test the implementation and effectiveness of a community health worker (CHW)-led hypertension control program within the national primary care system in Puno, Peru. Methods We will recruit 1068 adult participants with hypertension aged ≥ 18 years in Puno, Peru, via facility-based enrollment and community health fairs. Participants will be individually randomized (1:1) to either continue with usual care or participate in a 12-month CHW-led home-based hypertension control program consisting of blood pressure monitoring, medication adherence support, and healthy lifestyle counseling. Outcome development and reporting are guided by the Consolidated Framework for Implementation Research (CFIR), the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, and the Proctor et al. framework. Clinical effectiveness outcomes include mean change in systolic blood pressure (primary outcome), diastolic blood pressure, and HbA1C. Implementation outcomes include fidelity (i.e., CHW protocol adherence and dose), reach, adoption, sustainability, acceptability, and cost-effectiveness. Discussion The ANDES trial is testing the first CHW-led multicomponent strategy for hypertension and type 2 diabetes management in Peru. This type 2 hybrid trial will provide critical insights into the individual, community, and system-level factors necessary for successful implementation and effectiveness. These data can inform the future adaptation and scaling of the ANDES strategy in Peru and other LMICs, as well as influence policies at the system level to support this transition. Furthermore, by addressing both hypertension and diabetes, the ANDES strategy supports integrated care approaches advocated by the WHO HEARTS technical package, ultimately enhancing health outcomes and reducing morbidity and mortality in the region. Trial registration ClinicalTrials.gov, ID: NCT05524987 , Addressing Hypertension and Diabetes through Community-Engaged Systems in Puno, Peru (ANDES study), prospectively registered on September 1, 2021.